Impact of adherence to criteria on oncological outcomes of radical prostatectomy in patients opting for active surveillance: data from the PRIAS-JAPAN study. (4th June 2022) - Tohi, Yoichiro; Kato, Takuma; Miyakawa, Jimpei; Matsumoto, Ryuji; Sasaki, Hiroshi; Mitsuzuka, Koji; Inokuchi, Junichi; Matsumura, Masafumi; Yokomizo, Akira; Kinoshita, Hidefumi; Hara, Isao; Kawamura, Norihiko; et al.
Abstract: Objectives: This study aimed to evaluate whether oncological outcomes of radical prostatectomy differ depending on adherence to the criteria in patients who opt for active surveillance. Materials and methods: We retrospectively reviewed the data of 1035 patients enrolled in a prospective cohort of the PRIAS-JAPAN study. After applying the exclusion criteria, 136 of 162 patients were analyzed. Triggers for radical prostatectomy due to pathological reclassification on repeat biopsy were defined as on-criteria. Off-criteria triggers were defined as those other than on-criteria triggers. Unfavorable pathology on radical prostatectomy was defined as pathological ≥T3, ≥GS 4 + 3 and pathological N positivity. We compared the pathological findings on radical prostatectomy and prostate-specific antigen recurrence-free survival between the two groups. The off-criteria group included 35 patients (25.7%), half of whom received radical prostatectomy within 35 months. Results: There were significant differences in median prostate-specific antigen before radical prostatectomy between the on-criteria and off-criteria groups (6.1 vs. 8.3 ng/ml, P = 0.007). The percentage of unfavorable pathologies on radical prostatectomy was lower in the off-criteria group than that in the on-criteria group (40.6 vs. 31.4%); however, the differences were not statistically significant ( P = 0.421). No significant difference in prostate-specific antigen recurrence-free survival was observed between the groups during the postoperative follow-up period (median: 36 months) (log-rank P = 0.828). Conclusions: Half of the off-criteria patients underwent radical prostatectomy within 3 years of beginning active surveillance, and their pathological findings were not worse than those of the on-criteria patients. Abstract : Criteria adherence was not associated with unfavorable pathology with regard to radical prostatectomy in patients who opt for active surveillance.